2019
DOI: 10.5830/cvja-2019-015
|View full text |Cite
|
Sign up to set email alerts
|

The effects of HIV/AIDS on the clinical profile and outcomes post pericardiectomy of patients with constrictive pericarditis: a retrospective review

Abstract: Objective: The clinical profile and surgical outcomes of patients with constrictive pericarditis were compared in HIV-positive and-negative individuals. Methods: This study was a retrospective analysis of patients diagnosed with constrictive pericarditis at Inkosi Albert Luthuli Central Hospital, Durban, over a 10-year period (2004-2014). Results: Of 83 patients with constrictive pericarditis, 32 (38.1%) were HIV positive. Except for pericardial calcification, which was more common in HIV-negative subjects (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Constrictive pericarditis may also occur with HIV-associated pericardial disease (214) and is defined as impedance to diastolic filling due to a thickened fibrotic pericardium that may lead to HF (214). For example, Naidoo et al (141) showed that 38% of patients recruited with constrictive pericarditis were also HIV-positive. Because there are treatments for constrictive pericarditis, further studies are recommended to better understand the pathophysiology of this condition and also to determine the reasons for the relatively poor prognosis for HIV-positive individuals.…”
Section: Pericarditismentioning
confidence: 99%
“…Constrictive pericarditis may also occur with HIV-associated pericardial disease (214) and is defined as impedance to diastolic filling due to a thickened fibrotic pericardium that may lead to HF (214). For example, Naidoo et al (141) showed that 38% of patients recruited with constrictive pericarditis were also HIV-positive. Because there are treatments for constrictive pericarditis, further studies are recommended to better understand the pathophysiology of this condition and also to determine the reasons for the relatively poor prognosis for HIV-positive individuals.…”
Section: Pericarditismentioning
confidence: 99%
“…5 , 6 TBP is the leading cause of pericardial disease in areas with a high TB burden, particularly where human immunodeficiency virus (HIV) infection is prevalent. 7 , 8 However, adverse events can be reduced with effective treatment, which is dependent on accurate diagnosis, which is still quite difficult in TBP. 9 In early pericarditis with massive pericardial effusion, pericardial puncture can be performed to obtain a pericardial fluid specimen for adenosine deaminase (ADA) and other related tests.…”
Section: Introductionmentioning
confidence: 99%